Estimation of Sustainable Harvest Quota and Financial Analysis of Rusa timorensis in Intensive Captive Breeding - Sormin, Juliana; Santosa, Yanto; Haneda, Noor Farikhah (Media Konservasi, 2025)
Captive breeding of Rusa timorensis is one of the conservation efforts aimed at maintaining a balance between conservation and sustainable utilization. To effectively manage this balance, it is crucial to establish a utilization level that does not compromise the population's viability, which requires a thorough understanding of its demographic parameters. Furthermore, the sustainability of the breeding program itself is contingent upon its financial feasibility. This study aims to estimate demographic parameters, determine sustainable harvest quotas, and assess the financial feasibility of deer breeding in the Dramaga Research Forest, Indonesia. Methods included logbook analysis, observation, literature review, and interviews. Results show that the sustainable harvest quota under the intensive breeding system is 10 Rusa timorensis over the 2019–2023 period. The financial analysis demonstrates strong economic viability, with a Net Present Value of IDR 643 million at a 10% discount rate. The project demonstrated a Benefit-Cost Ratio exceeding 1, an Internal Rate of Return reaching 54%, and a rapid Payback Period of only 1.68 years. These findings suggest that intensive breeding can support both conservation objectives and economic profitability. Efficient management remains essential to ensure population sustainability and optimize benefits.